Radioiodination of andrographolide and its biodistribution in mice for inflammatory tracer - Jutti Levita; Cahya Nova A.; As’ari Nawawi; Slamet Ibrahim (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Andrographolide, a bioactive component of Andrographis paniculata (Burm.F) Nees, is the major lactone diterpenoidal bicyclic constituent in this plant which has proven to exert anti-inflammatory activity in vitro which was occurred via several mechanism, e.g inhibition of inducible nitric oxide synthase (iNOS), inhibition of radical oxygen species, and inhibition of NF-kappaB activation. The labeling with radionuclide is often used for therapy, detection and quantification of metabolites in the body. Even though the metabolites are very low in concentration they can be detected by the energy they emitted. Radionuclide can be used as radiotracer to detect whether drug really interacts with its target. The objective of this research is to synthesize 131I-labelled andrographolide and to study its biodistribution in mice to understand the location of its organ target. Indirect radioiodination of andrographolide wascarried out by using bromine as the leaving group and followed by fast iodination at 40oC, yielded 72.6 % purity of the labeled compound. Iodination was occurred through proton substitution at C-12. Then the andrographolide-131I was injected into lateral vein of mice’s tail to study its biodistribution. The compound was distributed in all organs with the highest accumulation occurred in the stomach (16.87 %/gram organ). The result showed that inducing the animals with LPS caused inflammation in the stomach and increased the production of prostaglandin as proven by the distribution of the radioligand in that organ.Key words: andrographolide, radioiodination, anti-inflammatory, biodistribution